Substitute ingredients for fishmeal in animal feed Oreochromis niloticus: A Meta-analysis on productive performance - Bruno Mendes Visoni; Thaise Pinto de Melo; Luciana Potter; Sharine Nunes Descovi; Leila Picolli da Silva (Ciência Rural, 2025)
ABSTRACT: The present study was performed with the aim of correlating previously published studies on the impact of using ingredients of animal and vegetable origin as substitutes for traditional fish meal on the performance of Nile Tilapia fingerlings. A comprehensive search carried out until February 2024 involving consultation in the Wiley Online Library, Web of Science, PUBMED databases resulted in the identification of 15 suitable articles, selected from a total of 2932 studies examined. This study evaluated two types of protein ingredients (10 and 20%) as substitutes for fishmeal. The greater the protein concentration of plant and animal ingredients in the Nile Tilapia diet was, the greater the influence of the initial weight on the heterogeneity of the data. It is also possible to note that the higher the concentration of the ingredients, the less heterogeneous the data. At lower concentrations (10%), it was possible to observe a greater influence on the specific growth of Nile Tilapia. However, more studies are being carried out to evaluate inclusions greater than 20% in the diet.